Examining the Impact of Microbial Compost from Anaerobic Digestion on Soil Fertility and Maize Crop Nutrient Uptake - Nisar, Amna Nisar; Kumbhar, Abdul Qadir; Gulzar, Ayesha; Aslam, Aiman; Nazeer, Sadia; Hiaz Ullah; Afnan, Zawat; Zeeshan, Muhammad; Fiaz Rasool; Ali, Mohsin (Indus Journal of Bioscience Research, 2024)
This research study was to evaluate the effects of combining microbial compost and mineral fertilizer on soil properties, maize growth, and nutrient uptake. Therefore, after selecting normal soil, 10 kg of soil was placed in each pot. Nine treatments with three replications were applied by using a Completely Randomized Design (CRD) for the study layout. The results revealed that the maximum plant height (101.73 cm), shoot fresh weight (69.36 g), shoot dry weight (128.6 g), root fresh weight (1.68 g), and root dry weight (0.89 g), as well as the highest content of nitrogen (1.66%), the highest phosphorus concentration (1.04%), and the maximum potassium concentration (2.13%) were noted in SF+MM + ½ NPK, while contents of iron (80.2 mg/kg), zinc (98.46 mg/kg), copper (78.66 mg/kg), and manganese (67.7 mg/kg) were also recorded in SF+MM + ½ NPK compared to other treatments. After harvesting maize crops, the lowest pH (7.27), highest EC (0.38 dS/M), and the highest contents of organic matter (1.03%) were recorded in SF+MM + ½ NPK. Maximum nitrogen content in soil (37 mg/kg), phosphorus content in soil (19.7 mg/kg), and potassium content in soil (105.8 mg/kg) were recorded in T8, while maximum contents of iron (4.88 mg/kg), zinc (1.80 mg/kg), copper (0.51 mg/kg), and manganese (1.95 mg/kg) were recorded in SF+MM + ½ NPK. The combination of SF+MM + ½ NPK showed to be the most effective treatment, whereas the usage of compost and chemical fertilizer alone remained the least effective.